Intra-specific Variation in the Social Behavior of Barbary macaques (Macaca sylvanus) - Amici, Federica; Widdig, Anja; von Fersen, Lorenzo; Lopez Caicoya, Alvaro; Majolo, Bonaventura (Frontiers in Psychology, 2021)
Non-human primates show an impressive behavioural diversity, both across and within species. However, the factors explaining intra-specific behavioural variation across groups and individuals are yet understudied. Here, we aimed to assess how group size and living conditions (i.e. captive, semi-free-ranging, wild) are linked to behavioural variation in 5 groups of Barbary macaques (N=137 individuals). In each group, we collected observational data on the time individuals spent in social interactions and on the group dominance style, along with experimental data on social tolerance over food and neophobia. Our results showed that differences in group size predicted differences in the time spent in social interactions, with smaller groups spending a higher proportion of time in close spatial proximity, but a lower proportion of time grooming. Moreover, group size predicted variation in dominance style, with smaller groups being more despotic. Social tolerance was affected by both group size and living conditions, being higher in smaller groups and in groups living in less natural conditions. Finally, individual characteristics also explained variation in social tolerance and neophobia, with socially integrated individuals having higher access to food sources, and higher-ranking ones being more neophobic. Overall, our results support the view that intra-specific variation is a crucial aspect in primate social behaviour, and call for more comparative studies to better understand the sources of within-species variation.